Segregated Anatomical Input to Sub-Regions of the Rodent Superior Colliculus Associated with Approach and Defense - Comoli, Eliane; Das Neves Favaro, Plínio; Vautrelle, Nicolas; Leriche, Mariana; Overton, Paul G.; Redgrave, Peter (Frontiers in Neuroanatomy, 2012)
The superior colliculus (SC) is responsible for sensorimotor transformations required to direct gaze towards or away from unexpected, biologically salient events. Significant changes in external world are signalled to SC through primary multisensory afferents, spatially organised according to a retinotopic topography. For animals, where an unexpected event could indicate the presence of either predator or prey, early decisions to approach or avoid are particularly important. Rodents' ecology dictates predators are most often detected initially as movements in upper visual field (mapped in medial SC), while appetitive stimuli are normally found in lower visual field (mapped in lateral SC). Our purpose was to exploit this functional segregation to reveal neural sites that can bias or modulate initial approach or avoidance responses. Small injections of Fluoro-Gold were made into medial or lateral sub-regions of intermediate and deep layers of SC (SCm/SCl). A remarkable segregation of input to these two functionally defined areas was found. (i) There were structures that projected only to SCm (e.g. specific cortical areas, lateral geniculate and suprageniculate thalamic nuclei, ventromedial and premammillary hypothalamic nuclei and several brainstem areas) or SCl (e.g. primary somatosensory cortex representing upper body parts and vibrissae and parvicellular reticular nucleus in the brainstem). (ii) Other structures projected to both SCm and SCl but from topographically segregated populations of neurones (e.g. zona incerta and substantia nigra pars reticulata). (iii) There were a few brainstem areas in which retrogradely labeled neurons were spatially overlapping (e.g. pedunculopontine nucleus and locus coreuleus). These results indicate significantly more structures across the rat neuraxis are in a position to modulate defense responses evoked from SCm, and that neural mechanisms modulating SC-mediated defense or appetitive behaviour are almost entirely segregated.